Genetics of neuroendocrine and carcinoid tumours. - Leotlela, P; Jauch, A; Holtgreve-Grez, H; Thakker, R (2003)
Neuroendocrine tumours (NETs) originate in tissues that contain cells derived from the embryonic neural crest, neuroectoderm and endoderm. Thus, NETs occur at many sites in the body, although the majority occur within the gastro-entero-pancreatic axis and can be subdivided into those of foregut, midgut and hindgut origin. Amongst these, only those of midgut origin are generally argentaffin positive and secrete serotonin, and hence only these should be referred to as carcinoid tumours. NETs may occur as part of complex familial endocrine cancer syndromes, such as multiple endocrine neoplasia type 1 (MEN1), although the majority occur as non-familial (i.e. sporadic) isolated tumours. Molecular genetic studies have revealed that the development of NETs may involve different genes, each of which may be associated with several different abnormalities that include point mutations, gene deletions, DNA methylation, chromosomal losses and chromosomal gains. Indeed, the foregut, midgut and hindgut NETs develop via different molecular pathways. For example, foregut NETs have frequent deletions and mutations of the MEN1 gene, whereas midgut NETs have losses of chromosome 18, 11q and 16q and hindgut NETs express transforming growth factor-alpha and the epidermal growth factor receptor. Furthermore, in lung NETs, a loss of chromosome 3p is the most frequent change and p53 mutations and chromosomal loss of 5q21 are associated with more aggressive tumours and poor survival. In addition, methylation frequencies of retinoic acid receptor-beta, E-cadherin and RAS-associated domain family genes increase with the severity of lung NETs. Thus the development and progression of NETs is associated with specific genetic abnormalities that indicate the likely involvement of different molecular pathways.